John Henry Newman and contemporary philosophy - Aquino, Frederick D.; Milburn, Joe (Routledge studies in nineteenth-century philosophy, 2025)
"While John Henry Newman's writings have long received the attention of historians, theologians, and literary critics, they have largely been neglected by philosophers. However, Newman's importance as a philosopher is just now beginning to be acknowledged. This volume brings together leading philosophers and Newman scholars to explore the contours of his philosophical thought and to show its relevance to contemporary philosophy. The chapters explore, develop, and evaluate Newman's thought considering recent work in epistemology, philosophy of religion, moral philosophy, and philosophy of education. John Henry Newman and Contemporary Philosophy will be of interest to scholars and advanced students interested in 19th-century philosophy, philosophy of religion, epistemology, moral philosophy, philosophy of education, and 19th-century religious thought"-- Provided by publisher